Impact of fertility levels and rice genotypes on yield, quality, and chemical properties of soil under tarai region of Uttarakhand - Anjali Bahuguna; Dr D K Singh; Supriya; Chandra, Subhash; Chaudhary, Amresh; Patel, Shashank (ORYZA-An International Journal of Rice, 2024)
A field experiment was conducted during kharif season of 2019 at Crop Research Centre of G.B. Pant University of Agriculture and Technology, Pantnagar (Uttarakhand) for evaluation of six rice genotypes (IET-27263, IET-26418, IET-26420, NDR-359, PD-19 and PD-26) under varying fertility levels (Control, 100% RDF, 150% RDF). Treatments were tested in Split Plot Design with three replications keeping fertilizer levels in main plots and genotypes in sub plots. Application of fertilizer at 150% RDF resulted in significantly higher grain and straw yield over all other fertilizer levels. The rice genotype IET-27263 produced highest grain, straw and biological yield over other genotypes. Similarly, total nitrogen, phosphorus and potassium content and uptake were also found to be increased significantly up to 150% RDF. Similarly, maximum uptake of N and K in grain and straw was also recorded in genotype IET-27263. It can be concluded that application of fertilizers at higher dose up to 150% RDF is essential for obtaining higher yield of rice. The new rice genotype IET27263 was found superior to all other tested genotypes.